2017
DOI: 10.1038/s41598-017-03070-8
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-mediated p53 and Pten dual mutation accelerates hepatocarcinogenesis in adult hepatitis B virus transgenic mice

Abstract: The p53 mutation and altered Pten expression are two most common genetic events in Hepatitis B virus (HBV) infection related hepatocellular carcinoma (HCC). To confirm the causative role of p53 and Pten somatic mutation in HCC development, we established CRISPR/Cas9-mediated somatic gene disruption via hydrodynamic tail vein injection, allowing for in vivo targeting p53 and Pten simultaneously in adult HBV transgenic mice. Here we demonstrated that the utility of this approach resulted in macroscopic liver tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 44 publications
1
39
0
Order By: Relevance
“…Tward et al reported that about three quarters of mice developed HCC in 1 month after HGD injection of transposon carrying Met and β-catenin gene (Tward et al, 2007 ). Besides, the researchers also tried CRISPR/Cas9-mediated gene editing, which allowed rapid occurrence of liver tumors, by regulating oncogenes or tumor suppressor genes expression in somatic cells (Liu et al, 2017 ).…”
Section: Establishment Of Hepatocellular Carcinoma Models By Hgdmentioning
confidence: 99%
“…Tward et al reported that about three quarters of mice developed HCC in 1 month after HGD injection of transposon carrying Met and β-catenin gene (Tward et al, 2007 ). Besides, the researchers also tried CRISPR/Cas9-mediated gene editing, which allowed rapid occurrence of liver tumors, by regulating oncogenes or tumor suppressor genes expression in somatic cells (Liu et al, 2017 ).…”
Section: Establishment Of Hepatocellular Carcinoma Models By Hgdmentioning
confidence: 99%
“…92 To better address its underlying aetiology, Liu et al used HBV transgenic mice in combination with CRISPR/Cas9 mediated deletion of p53 and Pten. 93 Although the authors deleted the same 2 tumour suppressor genes as in a previous study, 47 their tumours presented as HCC not ICC and were cytokeratin 19-negative. The reason for this discrepancy is unclear despite the distinct settings, namely carbon tetrachloride or transgenic HBV.…”
Section: Intrahepatic Cholangiocarcinomamentioning
confidence: 84%
“…Importantly, several of these miRNAs target the main inhibitor of the PI3K/AKT pathway, PTEN protein, and its mutations were found in HCC patients [ 42 ]. In accordance, PTEN deficient mice have been shown to develop steatosis, hepatomegaly, and HCCs [ 43 , 44 ].…”
Section: Molecular Mechanisms Involved In Nash-related Hccmentioning
confidence: 95%